Émile Durkheim in the Pampas: The reception of his ideas in Argentina and Uruguay (1895 -1947) - Vila, Esteban Ezequiel (2025)
The present work aims to study the reception of Emile Durkheim’s ideas and those of his disciples among the chairs of sociology at the Universities of Buenos Aires and Córdoba in Argentina, and the University of the Republic in Uruguay, between 1895 and 1947. This study recognizes three periods of reception: the first covers the initial appearance of Durkheim in the Río de la Plata from 1895 to 1915, when the approach to this sociological school was mainly limited to The Rules of Sociological Method and, secondarily, The Division of Labour in Society. The second period comprises the years 1915-1933, when the readings of Durkheimian sociology are extended to other works such as The Elementary Forms of Religious Life, although its most outstanding feature was its comparison withGerman sociologies. Finally, the third period (1933-1947) involves a re-interpretation of Durkheim’s doctoral thesis in Argentina, creating a pre-functionalist thought, while in Uruguay this did not take place.